Engineering Musculoskeletal Tissue Interfaces - Bayrak, Ece; Yilgor Huri, Pinar (Frontiers in Materials, 2018)
Tissue engineering aims to bring together biomaterials, cells and signaling molecules within properly designed microenvironments in order to create viable treatment options for the lost or malfunctioning tissues. Design and production of scaffolds and cell-laden grafts that can mimic the complex structure and function of native tissues are among the most important elements of tissue engineering strategy. Although all tissues have their own complex structure, an even more complex case in terms of engineering a proper carrier material is encountered at the tissue interfaces, where two distinct tissues come together. The interfaces in the body can be examined in four categories; cartilage-bone and ligament-bone interfaces at the knee and the spine, tendon-bone interfaces at the shoulder and the feet and muscle-tendon interface at the skeletal system. These interfaces are seen mainly at the soft-to-hard tissue transitions and they are especially susceptible to injury and tear due to the biomechanical inconsistency between these tissues where high strain fields are present. Therefore, engineering the musculoskeletal tissue interfaces remain a challenge. This review focuses on recent advancements in the development of strategies for musculoskeletal interface engineering using different biomaterial-based platforms and surface modification techniques.